Unregistered Marriage Without A Nasab Guardian In Tanjung Pinggir: Islamic And Indonesian Law Perspectives - Bima Hidayatul Aqib; Nurul Huda Prasetiya (JURNAL ILMU SYARIAH, 2026)
Unregistered marriage without a nasab guardian remains prevalent in parts of Indonesian society and creates uncertainty regarding marital validity and the legal protection of women and children. This study examines the practice of such marriages in Tanjung Pinggir Village, Siantar Martoba District, and assesses their validity and implications from the perspectives of Islamic law, the Compilation of Islamic Law, and Indonesian positive law. The study employed normative-empirical legal research with a qualitative approach. Primary data were collected through interviews with three couples in unregistered marriages without a lawful nasab guardian, supported by observations and documentation; participation was voluntary; informed consent addressed the legal sensitivity of the information disclosed; and all identities were anonymized. Secondary data were obtained from the Qur'an, hadith, classical jurisprudence, legislation, and relevant scholarly literature. The data were analyzed descriptively by reducing, classifying, comparing, and interpreting field findings and legal norms. The results reveal three problematic practices: assigning an unrelated man as a nasab guardian, appointing a wali muhakkam without following the mechanism for a state-appointed guardian, and conducting a marriage while the woman remained legally bound to a previous husband. These practices were primarily driven by limited legal knowledge, while economic pressure reinforced the case in one instance. Under the legal framework applied in Indonesia, these marriages did not comply with guardianship and marriage-registration requirements, thereby weakening legal certainty and the protection of wives and children; the third case, in particular, could have been resolved through the readily available statutory ground for divorce under Article 116(c) of the Compilation of Islamic Law rather than through an unauthorized second marriage. The study concludes that legal education, access to a state-appointed guardian, and marriage registration must be strengthened to prevent similar practices. Keywords: Indonesian positive law; Islamic law; nasab guardian; unregistered marriage; wali muhakkam